Different treatment approaches for the localized gingival overgrowths: Case series - DOĞAN, BAŞAK; ÖZTÜRK ÖZENER, HAFİZE (My University, 2018)
ABSTRACT Localized gingival overgrowths belong to a common group of lesions designated as focal reactive overgrowths. They occur in response to chronic, low‑grade irritation caused by plaque or any other irritant. They have multifactorial etiopathology but exhibit similar clinical features with slight variations in patient complaints. Success of the lesions’ management depends on formation of healthy contours of the surgical area after excision of lesion and absence of a recurrence. The purpose of case series is to present 6 different cases of localized gingival overgrowths and their management with the following techniques: nonsurgical periodontal treatment, gingivectomy, flap surgery, free gingival graft, gingival unit, and connective tissue graft.
Different treatment approaches for the localized gingival overgrowths